Vision sur les grands défis - Myre, Mario (Assurances, 1994)
As President and Chief Executive Officer of Dale-Parizeau inc., a subsidiary of Sodarcan inc., the author presents his views on the challenges that lie ahead for the property insurance industry in the wake of the major upheaval and realignment of financial services. After reviewing the features of world reinsurance and property insurance markets, Mr. Myre examines three major challenges: • the need for a customer-focused approach (ex.: valued-added services); • the strategic realignment of insurance companies according to market constraints and their specific strengths and weaknesses (ex.: targetting specific market segments, specialization); • enhanced productivity and cost reduction (precesses and work methods).